Cell proliferation and survival mechanisms underlying the abnormal persistence of follicular cysts in bovines with cystic ovarian disease induced by ACTH - Salvetti, Natalia Raquel (2010)
Cystic ovarian disease (COD) is an important cause of infertility that affects cattle. Alterations in the ovarian micro-environment of females with follicular cysts could alter the normal processes of proliferation and programmed cell death in ovarian cells. Thus, the objective in the present study was to evaluate apoptosis and proliferation in induced ovarian cystic follicles in cows to investigate the follicular persistence. Stage of estrous cycle was synchronized in 10 heifers and 5 were then subjected to the induction of COD by administration of ACTH. After the ovariectomy number of in situ apoptotic cells by TUNEL assay, active caspase-3, FAS/FASLG and members of the BCL2 family were compared by immunohistochemistry and multiplex PCR and cell proliferation by evaluation of Ki-67 protein and cyclin D1 and E mRNA. Significantly (p<0.05) lesser proliferative and apoptotic rates were found in cystic follicles from cows with COD compared with those with regular cycles. The relatively minimal proliferation found by immunohistochemistry with Ki-67 marker were confirmed by the gene expression of cyclin D1 and E. Lesser apoptotic rates were associated with decreased amounts of apoptotic-related proteins BAX, FASLG and caspase-3 as well as the in situ apoptosis detected by TUNEL assay, and increased amounts of the anti-apoptotic survival factor cellular BCL2 in the cystic follicles of the COD group. The BAX/BCL2 gene expression profile confirmed the immunohistochemical findings. Results from the present study indicate that cellular proliferation and apoptosis are altered in cystic follicles of cattle. The present study provides new insights into the molecular mechanisms underlying the aberrant persistence of follicular cysts and related diseases.